SIKAP SPIRITUAL GURU DALAM PEMBELAJARAN: (Studi Pada Guru Madrasah Aliyah Qodiriyah Harjowinangun Dempet Demak) - Taufikin, Taufikin (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2018)
Personal Competences of teacher in the Regulation of the Minister of National Education in 2008 are faithful, cautious and Consistent in applaying religious life and tolerant. Therefore, teachers should have consistency in implementing their spiritual attitudes in learning to be role models for learners. No exception Teachers in MA Qodiriyah Harjowinangun Demak Dempet especially who teach the clusters of Islamic Religious Education (Qur'an Hadith, Fiqh, Aqidah Ahlak and SKI). To know more about their spiritual attitudes, used field research with qualitative approach, data obtained by observation and interview then analyzed descriptively with phenomenology approach. From this study it is found that MA Qodiriyah teachers a have implemented the spiritual potential of nafsaniyyah (consisting of reason, heart and lust) and ruhaniyyah (consisting of spirit and fitrah). Then they implement with various practices outside learning, among others, memorize the Qur'an certain letters, istighatsah, night prayers, and follow tarekat. While at the learning start with praying together and keep holy with wudlu.